The effect of lysine and valine fed during lactation on sow and litter lactation performance - B T Richert; R G Campbell; S Kershaw; S A Blum; Robert D Goodband; Michael D Tokach; Jim L Nelssen (Kansas Agricultural Experiment Station Research Reports, 1994)
Two hundred two sows (98 parity 1 and 104 parity 2 sows) were used in a 2 x 3 factorial arrangement of treatments to determine the effect of dietary valine and lysine on sow lactation performance. Treatments included two levels of lysine (.8 or 1.2%) and three valine to lysine ratios (80, 100, 120% of lysine). This experiment was conducted at a research farm of a production facility in New South Wales, Australia from January to March, 1994. For all sows, increasing dietary lysine increased litter weaning weight and litter weight gain and reduced sow weight loss. Increasing dietary valine tended to increase litter weight gain. Parity 1 sows had a greater response in litter weight gain to dietary lysine than parity 2 sows. Parity 1 sows also exhibited a linear increase in litter weight gain as dietary valine increased. Parity 2 sows had an increase in litter weight gain at the low lysine level but a decrease in litter weight gain at the high lysine level with increasing valine in the diet. Both parities had a similar reduction in sow weight loss with increasing dietary lysine. The data also were separated into sows that weaned 10 or more pigs and sows that weaned fewer than 10 pigs. Sows that weaned 10+ pigs had a greater increase in litter weaning weight and litter weight gain when dietary lysine was increased from .8 to 1.2 %. These sows also had a linear increase in litter weaning weights and litter weight gain as valine increased. Sows that weaned fewer than 10 pigs had no response to increasing lysine or valine. Serum urea nitrogen was increased by increased dietary lysine but was not affected by valine. The results demonstrate the need to increase dietary lysine and valine as milk production increases. The high-producing sow (10+ pigs weaned) requires increased lysine and valine to maximize litter growth rate and minimize sow weight loss. The independent increases in litter weaning weights from adding lysine and valine suggest separate modes of action in the high-producing sow for these amino acids in milk synthesis.; Swine Day, Manhattan, KS, November 17, 1994
Keywords: Swine day; 1994; Kansas Agricultural Experiment Station contribution; no. 95-175-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 717; Swine; Lysine; Valine; Lactation; Sows